High-resolution vessel wall magnetic resonance imaging for depicting imaging features of unruptured intracranial vertebrobasilar dissecting aneurysms - Sui, Binbin (J Int Med Res, 2021)
OBJECTIVE: To demonstrate the application value of high-resolution vessel wall magnetic resonance imaging (HR-VW-MRI) for depicting the imaging features of unruptured intracranial vertebrobasilar dissecting aneurysms (VBDAs). METHODS: HR-VW-MRI data of 49 patients with suspected unruptured VBDAs were retrospectively analyzed. The presence of intramural hematomas (IMH), double lumens, intimal flaps, and outer diameter enlargements were recorded. Specificity and sensitivity were calculated for both two-dimensional (2D) and three-dimensional (3D) sequences. Additionally, IMH volumes were measured and posterior inferior cerebellar artery (PICA) involvement was analyzed. RESULTS: Thirty-five VBDAs were confirmed in 34 patients. The overall sensitivity and specificity were 0.889 (95% confidence interval [CI]: 0.730–0.964) and 0.769 (95% CI: 0.460–0.938) for 2D sequences, and 0.917 (95% CI: 0.764–0.978) and 0.846 (95% CI: 0.537–0.973) for 3D sequences, respectively. Intimal flaps were detected in 57.1%, 87.5%, and 71.4% of all cases on 2D pre-contrast T1-weighted, contrast-enhanced T1-weighted, and 3D T1-weighted black-blood (BB) images, respectively. There was no significant difference in IMH volume between 3D T1-weighted BB and magnetization-prepared rapid gradient-echo sequences. PICA involvement was best visualized using 3D T1 sequences. CONCLUSION: 3D T1-weighted BB MRI provided good visualization of VBDA features, with large coverage, and was useful for detecting dissection flaps.